Miltochrista nigrococcinea, a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae) - Bayarsaikhan, Ulziijargal; Im, Kyung-Hoan; Bae, Yang-Seop; Volynkin, Anton V. (Zootaxa, 2019)
Miltochrista Hübner is one of the largest genera of lichen-moths (family Erebidae, subfamily Arctiinae, tribe Lithosiini) including more than 160 valid species and widely distributed in Oriental and Palaearctic Regions. The genera Miltochrista and the related Asura Walker for a long time were treated in a wide sense. Hampson (1900) considered the generic names Barsine Walker, Ammatho Walker, Sesapa Walker, Cabarda Walker, Mahavira Moore, Korawa Moore and Gurna Swinhoe as synonyms of Miltochrista, and genera such as Lyclene Moore, Nepita Moore, Cyme Felder and Adites Moore under Asura. Holloway (2001) revived the genera Barsine (=Ammatho, Mahavira and Korawa), Cabarda, Lyclene, Nepita, Cyme and Adiles and transferred most of species of Miltochrista to Barsine and Cabarda, and most of species of Asura to Lyclene, Adiles, Cyme and Nepita. Later, the genera Gurna and Sesapa were also revalidated by Volynkin (2016; 2017a). According to Holloway (2001) the main differences between Miltochrista and Lyclene are wing venation and number of cornuti. However, these features may vary within the genus, while the ground plan of clasping apparatuses of the two taxa is the same. For this reason, Kirti & Singh (2016) synonymized Lyclene with Miltochrista. Volynkin et al. (2018) confirmed this synonymy and considered Miltochrista sensu Holloway (2001) as the M. miniata (Forster) species-group only.